PENGARUH PENGGUNAAN MASKER MENTIMUN TERHADAP PERAWATAN KULIT WAJAH BERJERAWAT - Lindawati, Ayu; Hayatunnufus, Hayatunnufus; Yanita, Merita (Journal of Home Economics and Tourism, 2017)
This study is based on the number of adults and adolescents aged 17-25 years, has a type of inflammantory pimple type Papula, due to acne lack of confidence when doing the activity. This study aims to analyze the effectiveness of the use of cucumber mask against acne facial skin care with assessment indicators include color, diameter and amount of acne. This research type Quasi Experiment with Design Nonequivalent Control Group Design. The object of this study is students who have facial skin acne, amounting to nine people samples.Teknik sampling purposive sampling conducted volunteer. The data collected from this research are primary data. Prior to hypothesis testing it is necessary to test the analytical requirements to see normality and homogeneity test, to test the hypothesis used ANAVA test and continued Duncan test. Based on the results of this study, showed that in the XI group there was no significant effect, X2 there was a significant effect as well as on X3 showed significant results on color indicator, diameter and amount of acne. Differences in the effect of cucumber mask use among the three treatment groups showed significant results with a 0.000 score, because 0.000 <0.050 the hypothesis was accepted.Keywords: Cucumber, Acne Face Skin